TRIM21 promotes type I interferon by inhibiting the autophagic degradation of STING via p62/SQSTM1 ubiquitination in systemic lupus erythematosus - Li Chen; Ma Ang; Bai Yu; Liu Zitao; Tian Linghan; Wang Ziyuan; Ma Huaishun; Chen Zhengpu; Gao Zhengheng; Feng Shijie; Fu Ping (Acta Biochimica et Biophysica Sinica)
The cGAS-STING signaling pathway serves as a pivotal surveillance mechanism for cytosolic double-stranded DNA (dsDNA) detection in mammalian systems. While STING-mediated type I interferon production is crucial for host defense, sustained activation of this pathway contributes to autoimmune pathologies, including systemic lupus erythematosus (SLE). Maintaining immune homeostasis requires precise regulation of STING activity to prevent hyperactivation. Our study identifies TRIM21 as a novel positive regulator of cGAS-STING signaling in SLE pathogenesis. Our results demonstrate that TRIM21 overexpression stabilizes STING by suppressing autophagic degradation, whereas TRIM21 depletion accelerates this clearance process. Mechanistically, TRIM21 catalyzes the K63-linked polyubiquitylation of the selective autophagy receptor p62/SQSTM1, disrupting its interaction with STING. This post-translational modification prevents the sequestration of STING into autophagosomes, thereby stabilizing the adaptor protein and amplifying downstream type I interferon responses. Our findings reveal a previously unrecognized regulatory circuit in which TRIM21 orchestrates cross-talk between ubiquitin signaling and autophagy to control STING turnover. The TRIM21-p62 axis represents a potential therapeutic target for attenuating pathological interferon production in STING-dependent autoimmune disorders. This work advances our understanding of immune regulation by demonstrating how E3 ligase-mediated ubiquitin modifications modulate cargo recognition in selective autophagy pathways. The identified mechanism provides new insights into the molecular interplay between protein ubiquitylation and autophagic degradation in maintaining the innate immune balance, offering novel perspectives for developing targeted therapies against interferonopathies associated with cGAS-STING hyperactivity.